Practical guide on left atrial appendage closure for the non-implanting physician: an international consensus paper - Potpara, Tatjana; Grygier, Marek; Häusler, Karl Georg; Nielsen-Kudsk, Jens Erik; Berti, Sergio; Genovesi, Simonetta; Marijon, Eloi; Boveda, Serge; Tzikas, Apostolos; Boriani, Giuseppe; Boersma, Lucas V A; Tondo, Claudio; et al. (Europace, 2024)
A significant proportion of patients who suffer from atrial fibrillation (AF) and are in need of thromboembolic protection are not treated with oral anticoagulation or discontinue this treatment shortly after its initiation. This undertreatment has not improved sufficiently despite the availability of direct oral anticoagulants which are associated with less major bleeding than vitamin K antagonists. Multiple reasons account for this, including bleeding events or ischaemic strokes whilst on anticoagulation, a serious risk of bleeding events, poor treatment compliance despite best educational attempts, or aversion to drug therapy. An alternative interventional therapy, which is not associated with long-term bleeding and is as effective as vitamin K anticoagulation, was introduced over 20 years ago. Because of significant improvements in procedural safety over the years, left atrial appendage closure, predominantly achieved using a catheter-based, device implantation approach, is increasingly favoured for the prevention of thromboembolic events in patients who cannot achieve effective anticoagulation. This management strategy is well known to the interventional cardiologist/electrophysiologist but is not more widely appreciated within cardiology or internal medicine. This article introduces the devices and briefly explains the implantation technique. The indications and device follow-up are more comprehensively described. Almost all physicians who care for adult patients will have many with AF. This practical guide, written within guideline/guidance boundaries, is aimed at those non-implanting physicians who may need to refer patients for consideration of this new therapy, which is becoming increasingly popular.
Keywords: síňové ouško; Hemorrhage; Left atrial appendage occlusion; Consensus; Humans; vitamin K; Stroke; dospělí; výsledek terapie; Left atrial appendage closure; lidé; Atrial Fibrillation; uzávěr ouška levé síně; cévní mozková příhoda; konsensus; Adult; Anticoagulation; lékaři; Thromboembolism; Treatment Outcome; Prevention; Vitamin K; tromboembolie; krvácení; Physicians; antikoagulancia; Atrial fibrillation; Atrial Appendage; Anticoagulants; Bleeding; fibrilace síní; Left Atrial Appendage Closure